CREATIVE ACCOUNTING PRACTICES FROM THE PERSPECTIVE OF ACCOUNTING EDUCATORS WITH PRACTICAL EXPERIENCE - Siti Aisyah; Muh Nasrun; Wahyuni (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2025)
This study examines the empirical influence of emotional intelligence, work motivation, rewards, and punishments on creative accounting practices. Utilizing an explanatory design, primary data was gathered from 30 accounting academic-practitioners via purposive sampling and analyzed using Multiple Linear Regression via SPSS. Results demonstrate that partially, emotional intelligence, work motivation, and rewards significantly influence creative accounting choices. Guided by the Theory of Planned Behavior, target-oriented motivation and incentives construct po sitive attitudes to exploit accounting flexibility, while emotional intelligence serves as an internal regulatory filter. Crucially, punishment yields a counterintuitive significant positive influence on creative accounting. Evaluated through Cognitive Dissonance Theory, rigid sanctions under demanding expectations generate severe professional duress; consequently, individuals experience intense psychological conflict and tactically utilize regulatory loopholes as a rationalized defensive mechanism to avoid career risks. Simultaneously, all variables exert a significant combined effect. Management must restructure controls away from fear-inducing climates toward supportive professional ecosystems.